The Angelica dahurica: A Review of Traditional Uses, Phytochemistry and Pharmacology - Zhao, Hui; Feng, Ya-Long; Wang, Ming; Wang, Jing-Jing; Liu, Tian; Yu, Jun (Frontiers in Pharmacology, 2022)
Angelica dahurica (A. dahurica) root is a famous edible medicinal herb that has been used in China for thousands of years. To date, more than 300 chemical constituents have been discovered from A. dahurica. Among these ingredients, coumarins and volatile oils are the major active compounds. Moreover, a few other compounds have also been isolated from the root of A. dahurica, such as alkaloids, phenols, sterols, benzofurans, polyacetylenes and polysaccharides. Modern pharmacological studies demonstrated that the root of A. dahurica and its active components displayed various bioactivities such as anti-inflammation, anti-tumor, anti-oxidation, analgesic activity, antiviral and anti-microbial effects, effects on the cardiovascular system, neuroprotective function, hepatoprotective activity, effects on skin diseases and so on. Based on these studies, this review focused on the research publications of A. dahurica and aimed to summarize the advances in the traditional uses, phytochemistry and pharmacology which will provide reference for the further studies and applications of A. dahurica.